Preparing Effective Narrative Evaluations for the Medical School Performance Evaluation (MSPE) - April O. Buchanan; Lisa Strano-Paul; Kris Saudek; Carla Lupi; Lee Jones; Mary Jo Wagner; Donna Elliott (Association of American Medical Colleges, 2022)
Introduction In 2016, the AAMC Medical School Performance Evaluation (MSPE) Task Force issued recommendations to standardize the MSPE but did not address the quality of the written narratives in that document. Narrative evaluations are hampered by code words, polite rhetoric, and bias to the detriment of students. To address this, the AAMC's Group on Student Affairs and Group on Educational Affairs convened an expert group to consider the state of narratives in the MSPE and develop resources to improve their quality. Methods A series of interactive workshops was developed and presented at an AAMC webinar and national meetings. A presentation outlining challenges and possible approaches to improvement was followed with large-group discussion and/or small-group breakout activity to analyze and improve upon sample clinical comments and create summary clerkship paragraphs. The initial webinar used polling questions and free-text prompts to gather feedback for future workshops. Anonymous survey responses were collected at the end of each subsequent workshop to determine perceived effectiveness and potential utility at participants' institutions. Results Over 680 administrators, faculty, and staff participated in the webinar or in one of four national-level workshops. Respondents agreed that the modules would be useful in faculty development and wanted to replicate their learning at their own institutions for overall better impact on the quality of MSPE narratives. Discussion This resource addresses an important gap in the medical education literature. A variety of stakeholders affirmed that these workshops have value in training writers to improve their narrative comments for the MSPE.